Literary and cultural facts for the study of the Armenian-Kypchak heritage - Zhiyembay Б.С.; Kossybayev, M.M.; Meirambekova Л.К. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
At the current time, turning to historical facts is a matter of great significance for the public life of Kazakhstan, since only a thorough study of documents related to the history of the country will help form knowledge about the history and future of our sovereign state. It is known that in the Middle Ages the rich heritage of the Qypchaks, who had founded the Desht-i-Qypchak state in Eurasia and contributed to world civilization and culture, was written in different alphabets at certain periods of history. Historical documents, written in Armenian graphics in Qypchak, are based on knowledge of religion, literature, history, law, philosophy, natural sciences and tell about the political, economic, historical and cultural spheres of the life of the ancient state. The Armenian-Qypchak heritage, since the 20th century, has been the subject of in-depth study of scientists, published in foreign academic editions, transcribed, supplemented by dictionaries and translations, its secrets are being revealed day by day. The term «ArmenianQypchak» was introduced by scientists, and the life and cultural ties of the medieval Qypchaks and Armenians became the basis for their research. Today there is aneed for a more detailed study of the linguistic features of the Armenian-Qypchak heritage, set out in different genre texts.